The prognostic implication of slug in all tumour patients – a systematic meta‐analysis. (22nd March 2016) - Huang, Cheng; Zhang, Ping; Zhang, Depu; Weng, Xisheng
Abstract: Background: E‐cadherin is an invasion suppressor molecule which counteracts tumour metastasis and progression. Slug, one of the crucial transcriptional repressors of E‐cadherin gene, has been widely reported on its prognostic role in patients with carcinoma, but the results are controversial. Thus, it is necessary to conduct a meta‐analysis to draw a convincing conclusion. Design: PubMed, Embase and Web of Science databases were searched for studies published until August 1st, 2015. Studies using immunohistochemistry (IHC) to detect the protein expression level in tumour tissues were set as protein group, while studies applying real‐time quantitative polymerase chain reaction (RT‐qPCR) to probe mRNA transcriptional level were set as mRNA group. Pooled hazard ratio (HR) and their corresponding 95% confidence interval (95% CI) were extracted to evaluate the prognostic role. Funnel plots, Begg's test and Egger's test were used to evaluate the publication bias. Sensitivity and heterogeneity analysis were also conducted. Results: The pooled HR of 23 studies in the protein group was 1·85 (95% CI: 1·51–2·28, I 2  = 55·4%, P  =   0·001), including 1·98 ((95% CI: 1·53–2·58, I 2  = 55·9%, P  =   0·004) for overall survival (OS) and 1·46 (95% CI: 1·18–1·82, I 2  = 52·0%, P  = 0·012) for progression‐free/ recurrence‐free/ disease‐free/ cancer‐free survival (PFS/RFS/DFS/CFS). The high expression of Slug in the protein group indicated poor prognosis of the tumour patients. However, the pooled HR of 6 studies in the mRNA group was 0·85 (95% CI: 0·48–1·53, I 2  = 77·2%, P  = 0·001), suggesting no statistical significance. Subgroup analysis was performed to avoid heterogeneity caused by tumour types. Besides, publication bias was not observed in all studies except for the mRNA transcription studies. Conclusions: The protein expression rather than mRNA transcription of Slug should be considered as a potent biomarker for poor prognosis of tumours, particularly head and neck cancer as well as lung and urinary carcinomas.